1999
DOI: 10.1002/(sici)1521-3773(19990917)38:18<2741::aid-anie2741>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perfluoroarene-Arene Interactions on the Phase Behavior of Liquid Crystalline and Polymeric Materials

Abstract: A stabilization of the liquid-crystalline mesophase and thus an enlarged temperature range of the mesogenic phase is achieved by adding perfluorotriphenylene to a chiral liquid-crystalline triphenylene. This mesophase is based on 1:1 perfluoroarene-arene interactions (see picture). In a polymer with triphenylenes as mesogens in the side chains, the addition of perfluorotriphenylene led to crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(114 citation statements)
references
References 7 publications
4
110
0
Order By: Relevance
“…In contrast to homocrystals of partners normally revealing the herringbone pattern, in complexes the neighboring arene and polyfluoroarene molecules are always oriented face-to-face. It was shown that arenepolyfluoroarene complexes can be used in crystal engineering, especially in the design and synthesis of advanced functional materials (for example, nematic [6] and discotic [7] liquid crystals, J aggregates [8], photochromic crystals [9], thin-film transistors [10], etc. ), in organizing the crystal packing suitable for topochemical dimerization or polymerization of unsaturated compounds [11], and even in template-directed cyclophane synthesis in the solution state [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to homocrystals of partners normally revealing the herringbone pattern, in complexes the neighboring arene and polyfluoroarene molecules are always oriented face-to-face. It was shown that arenepolyfluoroarene complexes can be used in crystal engineering, especially in the design and synthesis of advanced functional materials (for example, nematic [6] and discotic [7] liquid crystals, J aggregates [8], photochromic crystals [9], thin-film transistors [10], etc. ), in organizing the crystal packing suitable for topochemical dimerization or polymerization of unsaturated compounds [11], and even in template-directed cyclophane synthesis in the solution state [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among various non-covalent intermolecular interactions, arene-perfluoroarene (Ar H -Ar F ) interaction (32,33), known as a strong face-to-face interaction between perfluorinated and nonfluorinated aromatic rings. The approach was recently widely utilized to control supramolecular organization in reversible media (34)(35)(36) and also to create tightly packed molecular assemblies for electronic and optoelectronic applications (37,38). Although some other non-covalent interactions were well investigated for the realization of supramolecular self-assembled structures for use in NLO applications (39)(40)(41)(42), there are few reports concerning the use of the Ar H -Ar F interaction in EO materials to both assist dipole alignment during electric-filed poling and provide physical cross-linking for lattice hardening.…”
Section: Supramolecular Self-assembly Of Dendronized Nlo Chromophoresmentioning
confidence: 99%
“…Skabara and McCulloch et al reported the synthesis of regiosymmetric PTs having di-and tetrafluorobenzene, for example, polymers 56 and 57, via the FeCl 3 method, in which HH arrangements were used for the polymers (Scheme 3.13) [144]. Incorporation of perfluorinated aromatic rings is particularly interesting because these combinations of fluorinated and nonfluorinated π-electron systems enforce face-to-face π-stacking [145,146], and this increases electron affinity of the materials, leading to n-type organic semiconductors [147][148][149]. Fluorine-functionalized polymers 56 and 57 showed increased mobility in OFETs as compared to their parent nonfluorinated polymer.…”
Section: Regiosymmetric Polythiophenes With (Hetero)aromatic Ringsmentioning
confidence: 99%